2021
DOI: 10.3390/nu13020543
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting Properties of Bee Royal Jelly: Food of the Queens

Abstract: Royal jelly (RJ) demand is growing every year and so is the market for functional foods in general. RJ is formed by different substances, mainly carbohydrates, proteins, and lipids, but also vitamins, minerals, and phenolic or volatile compounds in lower proportion. Major royal jelly proteins (MRJP) are, together with 10-hydroxy-2-decenoic acid (10-HDA), key substances of RJ due to their different biological properties. In particular, 10-HDA is a unique substance in this product. RJ has been historically emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 185 publications
0
115
0
Order By: Relevance
“…Royal jelly (RJ) is a yellowish-white, creamy, acidic secretion from the mandibular and hypopharyngeal glands of young worker bees (the so-called nurses) of the Apis mellifera species [ 3 ]. It serves as the most important part of the honeybee larvae diet, including both worker and drone larvae, playing a major role in caste differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Royal jelly (RJ) is a yellowish-white, creamy, acidic secretion from the mandibular and hypopharyngeal glands of young worker bees (the so-called nurses) of the Apis mellifera species [ 3 ]. It serves as the most important part of the honeybee larvae diet, including both worker and drone larvae, playing a major role in caste differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific researchers have shown that royal jelly is a rich source of protein, carbohydrates, lipids, minerals, and vitamins, as well as female sex hormones. It was shown that royal jelly given to the mother larvae has a richer chemical composition (more sugars, juvenile hormones and acids) than that intended for other larvae [ 1 , 3 ]. Royal jelly lipids consist of fatty acids (90%), sterols, glycerides, and phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…Royal jelly is mainly constituted by water, proteins, carbohydrates, and lipids, as well as trace amounts of minerals, vitamins, and phenols, which are present in small quantities [ 72 ]. Proteins represent the most abundant fraction when considering only the dry matter of royal jelly [ 34 ], and the majority of them (82–90%, w / w ), the so-called Major Royal Jelly Proteins (MRJPs), are well studied [ 34 ].…”
Section: Nutritional Value Bioactive Components and Beneficial Properties Of Bee Productsmentioning
confidence: 99%
“…Some of the observed beneficial health effects include documented anti-inflammatory, antibacterial, antifungal, antiviral and antioxidant effects. Some honeybee products also showed antitumor effects [ 43 , 44 , 45 ]. The majority of the research has been done in preclinical setup, and the observed health effects are mainly attributed, but not confined entirely, to polyphenolic constituents.…”
Section: Health Benefits Of Bee Products With Focus On Regenerative Medicinementioning
confidence: 99%